The role of protein and amino acids in sustaining and enhancing performance - Institute of Medicine (U.S.). Committee on Military Nutrition Research (Washington, D.C. : National Academy Press, 1999)
It is a commonly held belief that athletes, particularly body builders, have greater requirements for dietary protein than sedentary individuals. However, the evidence in support of this contention is controversial. This book is the latest in a series of publications designed to inform both civilian and military scientists and personnel about issues related to nutrition and military service. Among the many other stressors they experience, soldiers face unique nutritional demands during combat. Of particular concern is the role that dietary protein might play in controlling muscle mass and strength, response to injury and infection, and cognitive performance. The first part of the book contains the committee's summary of the workshop, responses to the Army's questions, conclusions, and recommendations. The remainder of the book contains papers contributed by speakers at the workshop on such topics as, the effects of aging and hormones on regulation of muscle mass and function, alterations in protein metabolism due to the stress of injury or infection, the role of individual amino acids, the components of proteins, as neurotransmitters, hormones, and modulators of various physiological processes, and the efficacy and safety considerations associated with dietary supplements aimed at enhancing performance.
Committee summary and recommendations -- Protein and amino acids: physiological optimization for current and future military operational scenarios / Karl E. Friedl -- Overview of garrison, field, and supplemental protein intake by U.S. military personnel / Alana D. Cline, John P. Warber -- The energy costs of protein metabolism: lean and mean on Uncle Sam's team / Dennis M. Bier -- Regulation of muscle mass and function: effects of aging and hormones / Niels Moller, K. Sreekumaran Nair -- Effects of protein intake on renal function and on the development of renal disease / Mackenzie Walser -- Infection and injury: effects on whole body protein metabolism / Douglas W. Wilmore -- Inherent difficulties in defining amino acid requirements / D. Joe Millward -- Amino acid flux and requirements: counterpoint tentative estimates are feasible and necessary / Vernon R. Young -- Physical exertion, amino acid and protein metabolism, and protein requirements / Michael J. Rennie -- Skeletal muscle markers / Dympna Gallagher, Steven B. Heymsfield, Zi-Mian Wang -- Alterations in protein metabolism due to the stress of injury and infection / Robert R. Wolfe -- Amino acid and protein requirements: cognitive performance, stress, and brain function / Harris R. Lieberman -- Supplementation with branched-chain amino acids, glutamine, and protein hydrolysates: rationale for effects on metabolism and performance / Anton J.M. Wagenmakers -- Dietary supplements aimed at enhancing performance: efficacy and safety considerations / Timothy J. Maher.
Includes bibliographical references and index.
Print version record.
eBooks on EBSCOhost
Keywords: Proteins in human nutrition; Amino acids in human nutrition; Soldiers -- Nutrition -- United States; Amino acids in nutrition; Medicine, Military; Nutrition -- Requirements; Dietary Proteins; Amino Acids, Essential; Military Medicine; Nutritional Requirements; Physical Endurance -- physiology; Physical Fitness -- physiology; Protéines dans l'alimentation humaine; Acides aminés dans l'alimentation humaine; Acides aminés essentiels; Médecine militaire; Alimentation -- Besoins; SCIENCE -- Life Sciences -- Biochemistry; Nutrition -- Requirements; Medicine, Military; Amino acids in nutrition; Proteins in human nutrition; Amino acids in human nutrition; Soldiers -- Nutrition; United States